Cervical cancer prevention program in Nepal: a 'training of trainers' approach - Samantha Batman; Madan Piya; Sandhya Chapagain; Poonam Lama; Pabitra Maharjan; Binod Aryal; Maya Neupane; Shashwat Pariyar; Natacha Phoolcharoen; Vanessa Eaton; Vanessa Sarchet; Megan Kremzier; et al. (Inishmore Laser Scientific Publishing Ltd, 2023)
# Background Cervical cancer remains the leading cause of cancer-related death among Nepalese women. To this effect, Cancer Care Nepal established an international collaboration to implement a 'training of trainers' (TOT) program to expand the reach of cervical cancer prevention techniques. # Methods The Nepal cervical cancer prevention program began with an in-person TOT session in Kathmandu in November 2019. Due to the COVID-19 pandemic, two additional TOT courses were held in October and November 2021 with virtual support, didactic lectures from international faculty, and a hands-on component by Nepalese faculty. The Nepalese providers underwent training in these courses and then held further training in five collaborating centers across Nepal. Participants completed pre- and post-course knowledge assessments. The trainings were supplemented by the creation of a new Project ECHO® (Extension for Community Healthcare Outcomes) telementoring hub at Cancer Care Nepal. A capstone refresher course was held in November 2022. # Results 42 participants attended the initial TOT course in 2019. The two follow-up TOT courses held in October/November 2021 were two days long and included providers from five participating regions in Nepal. The courses included virtual didactic sessions followed by hands-on stations led by the Nepalese faculty who had participated in the 2019 TOT course. The stations included: visual inspection with acetic acid (VIA), colposcopy, thermal ablation, and loop electrosurgical excision procedure (LEEP). There were 41 participants in the October/November TOT courses. The trainers who received the TOT education then conducted local courses of similar content in each of the five regions for 152 local providers. Participants had improved mean knowledge scores after the training (0.70, 95% CI=0.67-0.72) in comparison to prior to training (0.50, 95% CI=0.47-0.53), p\<0.001. The program concluded with a capstone course in November 2022 attended by 26 participants. To date, 11 Project ECHO sessions have been held, with an average of 20 participants per session. # Conclusions Nepal's cervical cancer prevention program has increased the number of providers trained in cervical cancer prevention techniques. By increasing provider capacity, individuals will have increased access to cervical cancer screening and treatment of pre-invasive disease, hopefully decreasing the burden of cervical cancer in Nepal.